ANALISIS PENGARUH DANA PERIMBANGAN, PENDAPATAN ASLI DAERAH DAN JUMLAH PENDUDUK TERHADAP BELANJA DAERAH DI KABUPATEN/KOTA PROVINSI JAWA TIMUR TAHUN 2014 - 2016 - Yoga Pratama; Idah Zuhro; Faisal Abdullah (Jurnal Ilmu Ekonomi JIE, 2019)
Abstract: Regional Expenditures are all regional obligations recognized as deductions to net worth in the budget period. Factors affecting Regional Expenditures consist of Balancing Fund, Local Original Income, and Population. The purpose of this research is to know and to analyze the influence of level of Balancing Fund, Local Original Income, and Number of Resident to Regional Expenditure of Regency / City Government in East Java. The tool used in this research is panel data regression. The results of this study indicate that jointly Balancing Funds, Local Own Revenue and the Number of Population influential on Regional Expenditures District / City Government in East Java, with probability value 0.0000. While individually Balancing Fund has the positive and significant influence on the Regional Expenditure, with regression coefficient value of 0.302508 and probability value 0.0036. Local Revenue has a positive and significant impact on Regional Expenditure, with regression coefficient value of 0.569308 with probability value 0.0000. The number of residents has a positive and insignificant effect on regional expenditure, with a regression coefficient value of 3.294930 and probability value of 0.0907.Keywords: Regional Financial Management, Population